Protocol for a scoping review to identify and map intervention components of existing school-based interventions for the promotion of physical activity and cardiorespiratory fitness among school children aged 6–10 years old. Issue 10 (6th October 2020) - Brandes, Berit; Busse, Heide; Sell, Louisa; Christianson, Lara; Brandes, Mirko
Abstract : Introduction: Physical inactivity is known as a leading cause of mortality and tracks from childhood to adulthood. Many types of school-based single-component and multicomponent interventions to promote physical activity (PA) have been undertaken and evaluated, with mixed findings overall. Enlarging the intervention areas beyond the school setting is a promising approach. WHO's Health Promoting School (WHO HPS) framework is a holistic, setting-based approach where health is promoted through the whole school environment with links to other settings such as the home environment and wider community. In this paper, we outline our scoping review protocol to systematically review the published literature from the last 10 years to identify existing school-based interventions to promote PA and cardiorespiratory fitness among children aged 6–10 years old and to map intervention components according to the features of this framework. Methods and analysis: Arksey and O'Malley's scoping review methodology framework will guide the conduct of this review. We will search Medline, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Sports Medicine & Education Index, Education Resources Information Centre and CENTRAL and hand search the reference lists of key studies to identify studies appropriate for inclusion. Any empirical study that evaluated the effectiveness of a school-based intervention promoting PA and/or cardiorespiratory fitness in children aged 6–10 years old will be included. Two reviewers will independently screen all abstracts and full texts for inclusion. One reviewer will extract general information, study characteristics and intervention contents to classify them according to the features of the WHO HPS framework. Results will be synthesised narratively. Ethics and dissemination: Findings will be disseminated in conference presentations and peer-reviewed publications. A condensed version of the results will be made available for the public. Stakeholder meetings will be arranged to discuss and disseminate the findings.